Where and how to look - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A crisp and clear description, atlas-style, of more than a dozen farming systems, by region and by continent. Co-published with the World Bank, it shows how to use farming systems approaches to identify local, regional and international priorities...